Direct Hydrogenation of Nitroaromatics at Room Temperature Catalyzed by Magnetically Recoverable Cu@Fe2O3 Nanoparticles. (11th May 2020) - Borah, Biraj Jyoti; Bharali, Pankaj
Abstract : Metal embedded in metal oxide nanoparticles are active as catalyst in plethora of industrially important reactions. Herein, embedded Cu@Fe2 O3 nanoparticles was synthesized via a one step hydrothermal strategy which selectively catalyzes the hydrogenation of diverse nitroaromatics in H2 O at room temperature. The remarkable catalytic performance is due to the successful hybridization of metallic Cu and Fe2 O3 which in turn allows easy electroflipping between various oxidation states of Cu and Fe. Azo‐ and azoxy‐compounds are not formed during the catalyzed process. This evidently establish that the hydrogenation of nitroaromatics proceeds via direct route with >99% selectivity to the corresponding anilines. Abstract : Cu@Fe2 O3 nanoparticles favor direct hydrogenation of nitroaromatics at room temperature with >99% selectivity to corresponding anilines. The remarkable catalytic performance is due to the successful hybridization of metallic Cu and Fe2 O3 along with its magnetic separability.